Organizational Culture of Sukma Bangsa Learning School (Analytical Study of Learning Organization Primordial Value) - Agus Salim Salabi; Muhammad Anggung Manumanoso Prasetyo (Sukma: Jurnal Pendidikan)
This writing is a report study for the development of a learner school management model as well as the acceleration of educational completion with the goal of achieving sustainable education development at the Sukma Nation School of Lhokseumawe. The research focuses on the profile of the school of learners in Sukma Nation, as well as the program’s achievement and problems in its implementation. The research is qualitative in nature and employs survey methods. In terms of data gathered through documentation and interviews with relevant authorities, including focused group observations. The study also presents various manifestations of the Sukma Bangsa School innovations. The results specifically show that institution management refers to the implementation of five primordial grades of learner schools, namely personal mastery, dividing vision, mental models, sitem thinking, and group learning. According to the system, the succession of implementations is seen in changes in individual behavior ranging from knowledge mastery, information distribution, interpretation, and knowledge reminder. Furthermore, the school of learners’ leadership model has become a critical component of achieving school effectiveness.